2010
DOI: 10.1016/j.jasms.2010.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric studies of alkali metal ion binding on thrombin-binding aptamer DNA

Abstract: The binding sites and consecutive binding constants of alkali metal ions, (M ϩ ϭ Na ϩ , K ϩ , Rb ϩ , and Cs ϩ ), to thrombin-binding aptamer (TBA) DNA were studied by Fouriertransform ion cyclotron resonance spectrometry. TBA-metal complexes were produced by electrospray ionization (ESI) and the ions of interest were mass-selected for further characterization. The structural motif of TBA in an ESI solution was checked by circular dichroism. The metal-binding constants and sites were determined by the titration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 41 publications
(57 reference statements)
4
32
1
Order By: Relevance
“…However, the simulations predicted formation of 1:1 complex between 15-TBA and the ion, contrasting some studies suggesting 1:2 complex with vacant internal cavity of the quadruplex (46,47,70), with the ions located in the TGT and TT loop regions. Here, we address this issue with a combination of explicit solvent MD (30 new individual trajectories with aggregate length of 4 μs), hybrid QM/MM approach and ITC measurements.…”
Section: Discussioncontrasting
confidence: 85%
“…However, the simulations predicted formation of 1:1 complex between 15-TBA and the ion, contrasting some studies suggesting 1:2 complex with vacant internal cavity of the quadruplex (46,47,70), with the ions located in the TGT and TT loop regions. Here, we address this issue with a combination of explicit solvent MD (30 new individual trajectories with aggregate length of 4 μs), hybrid QM/MM approach and ITC measurements.…”
Section: Discussioncontrasting
confidence: 85%
“…The peak corresponding to two ammonium ions bound is the base peak for charge state 3-. The existence of a second cation binding site for the TBA in solution is currently controversial [30,[37][38][39]. Our mass spectrometry results clearly show the preservation of an additional specific ammonium cation by the TBA in addition to the one likely bound between the G-quartets, suggesting that a fraction of the population in solution possessed this additional cation.…”
Section: Esi-ms Spectra Suggest Additional Specific Ammonium Ion Bindmentioning
confidence: 59%
“…, has been studied by ESI-MS previously [28][29][30], but the detection of ammonium ion binding to TBA has not yet been reported. For the latter three sequences, the ammonium ion binding constants have been determined previously by NMR [25,27], so the theoretical distribution of ammonium ions captured between the G-quartets of the quadruplexes in solution can be calculated (Table 1).…”
mentioning
confidence: 99%
“…However, the localization of ions in the quadruplex and the stoichiometry of binding are not yet fully clear and, in certain cases, controversial results have been reported. Researches using NMR (Marathias and Bolton 2000), infrared multiphoton dissociation (IRMPD) and CD methods (Hong et al 2010) to study the TBA sequence have shown that the most likely form of 1:2 (TBA to K + ) stoichiometry is that which is depicted schematically in Fig. 1C.…”
Section: Stability Of Guanine Quadruplexes In Dna Aptamers At Presencmentioning
confidence: 99%